DEVELOPMENT CRACKERS OF SHALLOT PEEL FLOUR (ALLIUM CEPA L.) SUBSTITUTION - AGUSTIN, ARUM DWI; PURWASIH, RATIH; ARIANTI, ANISA PUTRI; MALIKAH, AVIDA HIKMATUL (International Journal of Applied Pharmaceutics, 2022)
Objective: One of the ingredients of red onion skin (Allium cepa L.) is a flavonoid that has the potential to be an antioxidant. Utilization of shallot peel (Allium cepa L.) is carried out by making functional food in the form of crackers. The aim of this study were to determine the of flavonoids contents and antioxidant activity in shallot (Allium cepa L.) peel flour crackers. Methods: The method used in this research is a quantitative analysis using the UV-Vis Spectrophotometer instrument at a wavelength of 418 nm for determining contents of flavonoids, and 518 nm for antioxidant activity. Results: The water and ash content of shallot (Allium cepa L.) peel flour was 9.6% and 0.5%. The average percentage of water content crackers of shallot (Allium cepa L.) peel flour substitution were 2%, 2.5%, and 3.02%, respectively. The average percentage of acid-insoluble ash content crackers of shallot (Allium cepa L.) peel flour substitution were 0.1%, 0.2%, and 0.23%, respectively. The hedonic test results showed respondents liked the aroma, color, and taste of crackers. Shallot (Allium cepa L.) peel flour and crackers of shallot (Allium cepa L.) peel flour substitution contain positive flavonoid compounds, total flavonoid content of shallot (Allium cepa L.) peel flour was 7.160 mgQE/g, and total flavonoid crackers of shallot (Allium cepa L.) peel flour substitution were 4.5591 mgQE/g, 4.8719 mgQE/g, and 5.189 mgQE/g respectively. The IC50 value of shallots peel flour crackers (Allium cepa L.) were 243.45, 224.57, and 206.78 ppm, respectively which are included in the medium level antioxidant. Conclusion: Shallots peel flour crackers fulfill the SNI standard with a water content were 2.0, 2.5, and 3.02% respectively and the acid-insoluble ash content were 0.1, 0.2, and 0.23% respectively. The shallots (Allium cepa L.) peel flour crackers have medium-level antioxidant activity with IC50 value were 243.45, 224.57, and 206.78 ppm, respectively.